Nilai Pendidikan Karakter Dalam Geguritan Wirotama - Wijaya Loka, I Made Sura; Sudarsana, I Ketut; Artayasa, I Wayan (Jurnal Penelitian Agama Hindu, 2019)
Geguritan is one form of Balinese literature. Writing geguritan is always bound by rules called padalingsa. Geguritan is useful as a guide and guideline in carrying out life about good behavior procedures. Wirotama Geguritan is one of the geguritan in Bali which is composed of several pupuh, namely Pupuh Dandang, Pupuh Sinom, Pupuh Semarandana, Pupuh Durma, Pupuh Ginada, Pupuh Ginanti, Pupuh Pangkur, and Pupuh Kumambang.The method used is the library method and documentation method, and the collected data is analyzed according to steps such as reduction, data presentation, and conclusion. Data that has been analyzed is presented in an informal method because it is presented using words, sentences and language from general to special or deductive-inductive.The results of the study concluded (1) The narrative structure of Geguritan Wirotama included: incidents, in the story there were seven incidents that began with I Lagawa finding a child in the forest; the plot used is a straight groove; characterizations found in Geguritan Wirotama, I Lagawalan I Sugati, Raden Dewidan, others; the setting or setting includes place and social settings; the theme in geguritan ways is self-confidence; the mandate contained in this geguritan is implementing something must be with confidence and sincerity so as to obtain good results. (2) Character Education Values ​​in Geguritan Wirotama are analyzed to find out and see how the story is delivered through the characters namely Wirotama, Radendewi, Sri Mahayani which is a symbol of the scale and niskala; (3) Wirotama's geguritan function.